Sierra Gorda 009: a new member of the metal-rich G chondrites grouplet - Ivanova, Marina A.; Lorenz, Cyril A.; Humayun, Munir; Corrigan, Catherine M.; Ludwig, Thomas; Trieloff, Mario; Righter, Kevin; Franchi, Ian A.; Verchovsky, Alexander B.; Korochantseva, Ekaterina V.; Kozlov, Vladimir V.; Teplyakova, Svetlana N.; et al. (Meteoritics & planetary science, 2020)
We investigated the metal-rich chondrite Sierra Gorda (SG) 009, a member of the new G chondrite grouplet (also including NWA 5492, GRO 95551). G chondrites contain 23% metal, very reduced silicates, and rare oxidized mineral phases (Mg-chromite, FeO-rich pyroxene). G chondrites are not related to CH-CB chondrites, based on bulk O, C, and N isotopic compositions, mineralogy, and geochemistry. G chondrites have no fine-grained matrix or matrix lumps enclosing hydrated material typical for CH-CB chondrites. G chondrites’ average metal compositions are similar to H chondrites. Siderophile and lithophile geochemistry indicates sulfidization and fractionation of the SG 009 metal and silicates, unlike NWA 5492 and GRO 95551. The G chondrites have average O isotopic compositions Δ17O>0‰ ranging between bulk enstatite (E) and ordinary (O) chondrites. An Al-rich chondrule from SG 009 has Δ17O>0‰ indicating some heterogeneity in oxygen isotopic composition of G chondrite components. SG 009’s bulk carbon and nitrogen isotopic compositions correspond to E and O chondrites. Neon isotopic composition reflects a mixture of cosmogenic and solar components, and cosmic ray exposure age of SG 009 is typical for O, E, and R chondrites. G chondrites are closely related to O, E, and R chondrites and may represent a unique metal-rich parent asteroid containing primitive and fractionated material from the inner solar system. Oxidizing and reducing conditions during SG 009 formation may be connected with a chemical microenvironment and possibly could indicate that G chondrites may have formed by a planetesimal collision resulting in the lack of matrix.
Gesehen am 30.06.2021